1998
DOI: 10.1088/0031-8949/58/2/011
|View full text |Cite
|
Sign up to set email alerts
|

The Viscous MHD Spectra – Application to Coronal Loop Heating and Stability

Abstract: We have derived the viscous MHD equilibrium and perturbed equations for current carrying cylindrical plasmas. We have considered compressible plasmas and, when the viscosity is introduced in the equation of motion it leads to a linearized vector second order perturbed equation for the fluid displacement, showing the appearance of non Hermitian operators. The Lagrangian representation is used to investigate the stability and we used the normal mode analysis to study the linearized equation. We applied our model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, it is suggested that viscosity plays a crucial role in the damping of waves over the other existing mechanisms such as phase mixing, ohmic heating, resonance absorption…etc [13]. The viscous MHD spectra for cylindrical plasma has been analysed by Santiago et al [14] and confirmed the viscosity as the dominant mechanism for coronal loop heating. In this work, we study the viscous damping of ASW at a single magnetic interface separating two incompressible viscous plasma media and estimate the damping length in the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that viscosity plays a crucial role in the damping of waves over the other existing mechanisms such as phase mixing, ohmic heating, resonance absorption…etc [13]. The viscous MHD spectra for cylindrical plasma has been analysed by Santiago et al [14] and confirmed the viscosity as the dominant mechanism for coronal loop heating. In this work, we study the viscous damping of ASW at a single magnetic interface separating two incompressible viscous plasma media and estimate the damping length in the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%